สมรรถนะของพยาบาลวิชาชีพที่ปฏิบัติงานในห้องอุบัติเหตุและฉุกเฉินโรงพยาบาลของรัฐ - ภัทรมน ทับสูงเนิน (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To explore the job competency of emergency nurses in government hospitals using the Delphi technique. Twenty one experts agreed to participate in this research, comprising one nurse educator, four nurse instructors, three physicians, five nurse managers and eight professional nurses working in the emergency department in government hospitals. Data were collected in three stages. First, all expert were asked to describe the competency of emergency nurses during emergencies in government hospitals. Second, data from the first round were analyzed by using content analysis and developed into a rating scale questionnaire. All items in the questionnaire ranked the level of competency by a prior panel of experts. Third, the median and interquatile range was used to analyze and correct the data in order to re-design the rating scale questionnaire. Finally, the participants finished the completed questionnaire and rating scale again. The data were analyzed again by median and interquatile range and selected competencies based on the following criteria: a) median more than 3.50, b) interquatile range less than 1.50. The major findings were classified into 11 competencies as follows: 1) emergency and crisis nursing practice consisting of 13 items. 2) triage and emergency symptom assessment consisting of 11 items. 3) advanced life support consisting of 6 items. 4) teamwork and coordinator consisting of 9 items. 5) communication consisting of 9 items. 6) characteristic and service behavior consisting of 10 items. 7) disaster management consisting of 11 items. 8) leadership consisting of 11 items. 9) laws, ethics and patient advocacy consisting of 10 items. 10) discharge planning and referral consisting of 8 items. 11) academic capacity of and quality improvement in accident and emergency nursing consisting of 11 items.